Anastomotic complications after robot-assisted laparoscopic and open radical prostatectomy. (3rd July 2016) - Jacobsen, André; Berg, Kasper Drimer; Iversen, Peter; Brasso, Klaus; Røder, Martin Andreas
Abstract: Objective Anastomotic complications are well known after radical prostatectomy (RP). The vesicourethral anastomotic technique is handled differently between open and robotic RP. The aim of the study was to investigate whether the frequency of anastomotic leakages and strictures differed between patients undergoing retropubic radical prostatectomy (RRP) and robot-assisted radical prostatectomy (RARP) and to identify risk factors associated with these complications.Materials and methods The study included 735 consecutive patients who underwent RRP ( n = 499) or RARP (236) at the Department of Urology, Rigshospitalet, Denmark, in a complete 3 year period from 2010 to 2012. Univariate and multivariate logistic regression analysis was used to analyse associations between surgical procedure (RRP vs RARP) and anastomotic complications. Analyses included age, smoking status, diabetes, hypertension, surgeon, prostate volume and anastomotic leakage as variables. Owing to a low number of events, multivariable analyses only included smoking status, diabetes and prostate volume for anastomotic leakage, and age, smoking status, prostate volume and anastomotic leakage for anastomotic strictures.Results The frequency of anastomotic leakage was 2.9%. Anastomotic stricture was seen in 4.9% of patients during follow-up. No differences were found in the frequency of anastomotic leakage ( p = 0.35) or strictures ( p = 0.35) between RRP and RARP. Univariate analysis demonstrated an association between surgeon and the risk of anastomotic strictures in RRP patients ( p = 0.02). No other independent risk factors were identified.Conclusion Overall, the anastomotic complication rate in this cohort is similar to other published reports. No obvious risk factors for anastomotic complications could be identified, which in part was due to the low number of events.